Heat Shock Proteins in Human Perilymph: Implications for Cochlear Implantation. Issue 1 (January 2018) - Schmitt, Heike; Roemer, Ariane; Zeilinger, Carsten; Salcher, Rolf; Durisin, Martin; Staecker, Hinrich; Lenarz, Thomas; Warnecke, Athanasia
Abstract : Objective: Biomarkers reflecting the etiology and pathophysiology of inner ear diseases are limited. Evaluation of proteins in the perilymph may improve our understanding of inner ear disease. Heat shock proteins (HSP) belong to a superfamily of stress proteins and promote refolding of denatured proteins. The aim of the study was to analyze HSP in human perilymph and to identify possible correlation with audiological and etiologic data. Methods: Sampling of the perilymph was performed during cochlear implantation and vestibular schwannoma removal. Individual proteins were identified by a shot-gun proteomics approach by orbitrap mass spectrometry. Expression of HSP genes was determined in human cochlear tissue that was obtained during transcochlear surgeries. Results: Ten subgroups of HSP were identified in human perilymph samples. Increased levels of HSP were detected in a higher percentage in the perilymph of patients with residual hearing when compared with patients with no residual hearing in cochlear implantation. In patients with complete preservation of residual hearing, HSP 90 is identified in a lower percentage whereas HSP 70 1A/1B and 6 was identified in all the samples. Constitutive expression of HSP family members was verified in normal cochlear tissue. Conclusion: The 10 HSP variants are not identified in all the perilymph samples, but in a higher proportion in patients with residual hearing compared with patients with no residual hearing. In-depth proteome analysis of perilymph samples in correlation to patients' audiogram data shows an increased concentration of HSP in patients with residual hearing. An increase in specific HSP in patients with loss of residual hearing after cochlear implantation was not observed.